2006
DOI: 10.1007/s00424-006-0104-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple types of Na+ currents mediate action potential electrogenesis in small neurons of mouse dorsal root ganglia

Abstract: Small (<25 microm in diameter) neurons of the dorsal root ganglion (DRG) express multiple voltage-gated Na(+) channel subtypes, two of which being resistant to tetrodotoxin (TTX). Each subtype mediates Na(+) current with distinct kinetic property. However, it is not known how each type of Na(+) channel contributes to the generation of action potentials in small DRG neurons. Therefore, we investigated the correlation between Na(+) currents in voltage-clamp recordings and corresponding action potentials in curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 44 publications
7
31
1
Order By: Relevance
“…Increased functional availability of TRPM8 then may account for the avoidance of cold temperatures by TRPC5 −/− mice. Reminiscent of our findings in TRPC5 −/− mice, the compensatory replacement of functionally related tetrodotoxin-sensitive ion channels in Nav1.8-deficient mice (40) partially restored the loss of Nav1.8 function in the null-mutant nerve endings but not in their cultured DRG neurons (30,41). In both cases, the result is protection from cold via functionally overlapping but molecularly independent cold-detection mechanisms.…”
Section: Discussionsupporting
confidence: 72%
“…Increased functional availability of TRPM8 then may account for the avoidance of cold temperatures by TRPC5 −/− mice. Reminiscent of our findings in TRPC5 −/− mice, the compensatory replacement of functionally related tetrodotoxin-sensitive ion channels in Nav1.8-deficient mice (40) partially restored the loss of Nav1.8 function in the null-mutant nerve endings but not in their cultured DRG neurons (30,41). In both cases, the result is protection from cold via functionally overlapping but molecularly independent cold-detection mechanisms.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies suggested that PNH in diabetic patients could be a consequence of increased persistent nodal Na v -currents (Misawa et al, 2009). As these currents are mainly mediated by Na V 1.9 TTX-resistant (TTX-R) Na vchannels (Matsutomi et al, 2006), we tested the sensitivity of CAPs to TTX. The residual CAP amplitude was similar in WT and db/db nerves after exposure to 100 nM TTX (respectively 38 Ϯ 2% and 37 Ϯ 6%) and 1 M TTX (Ͻ2% for both tested genotypes).…”
Section: Resultsmentioning
confidence: 99%
“…We defined DRG neurons that were smaller than 25 µm in diameter as small neurons (26), and small neurons thus defined were used throughout the study. We employed KO DRG neurons (6,12,13) in addition to WT DRG neurons in this study. Unless otherwise specified, the experiments were performed in neurons from WT DRG.…”
Section: +mentioning
confidence: 99%
“…Consequently, a possible involvement of I NaN has not been taken into consideration. In this study, therefore, we investigated the effect of PGE 2 on isolated I SNS or I NaN using wild-type (WT) as well as the Na V 1.8 knock-out (KO) mice (6,12,13). Unexpectedly, PGE 2 had no detectable effect on I SNS or I NaN , raising a question regarding the modulatory role of PGE 2 on TTX-R Na + current in inflammatory hyperalgesia.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation